Histone H3 lysine 4 methylation is mediated by Set1 and promotes maintenance of active chromatin states in fission yeast - Noma, Ken-ichi (The National Academy of Sciences, 2002)
Methylation of histone H3 at lysine 4 (H3 Lys-4) or lysine 9 (H3 Lys-9) is known to define active and silent chromosomal domains respectively from fission yeast to humans. However, in budding yeast, H3 Lys-4 methylation is also necessary for silent chromatin assembly at telomeres and ribosomal DNA. Here we demonstrate that deletion of set1, which encodes a protein containing an RNA recognition motif at its amino terminus and a SET domain at the carboxy terminus, abolishes H3 Lys-4 methylation in fission yeast. Unlike in budding yeast, Set1-mediated H3 Lys-4 methylation is not required for heterochromatin assembly at the silent mating-type region and centromeres in fission yeast. Our analysis suggests that H3 Lys-4 methylation is a stable histone modification present throughout the cell cycle, including mitosis. The loss of H3 Lys-4 methylation in set1Δ cells is correlated with a decrease in histone H3 acetylation levels, suggesting a mechanistic link between H3 Lys-4 methylation and acetylation of the H3 tail. We suggest that methylation of H3 Lys-4 primarily acts in the maintenance of transcriptionally poised euchromatic domains, and that this modification is dispensable for heterochromatin formation in fission yeast, which instead utilizes H3 Lys-9 methylation.